PENERAPAN METODE DISKUSI UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Muhkarom, Muhkarom (MEDIA DIDAKTIKA, 2021)
The purpose of the study is the application of discussion methods can improve student learning outcomes in learning Citizenship Education in Organization material. This study uses the Classroom Action Research (CAR) method using two cycles. Each cycle consists of four stages, namely planning, implementation, observation and reflection. Data collection is done with student observation sheets and test results in each cycle. Then the data is analyzed by quantitative analysis and qualitative analysis. The results of the study can be seen from the presentation of the average activity of students in the first cycle is 69 categories are quite active and have increased in the second cycle to 81 active categories. The completeness of student learning outcomes in the first cycle was 5 students (62.5%) and experienced an increase in the second cycle to 8 students (100%). The conclusion of the study shows that the use of discussion methods can improve student learning outcomes in learning Citizenship Education in the 2017/2018 Academic Year Organization material.